النشاط الجمعوي وعلاقته بتنمية سلوك المواطنة لدى أعضاء جمعيات بلدية عين الملح)دراسة ميدانية( - بن كيحول, محمد (Université de M'sila, 2018)
Collective activities are one of the most important social phenomena in our current Algerian society, With the aim of providing assistance to various segments of society, While in many countries it has a history and an active role in its development, And stability, With its positive volunteerism, which shares and supports the behavior of citizenship, Therefore, in this field study, we try to identify the extent to which collective action influences the development of citizenship behavior, Through a sample of 45 members of three active associations In the Municipality of Ain El-Melh State of M'sila, By asking the following questions: - Are there statistically significant differences in the behavior of citizenship due to the variable level of study? - Are there statistically significant differences in the behavior of citizenship due to the variable activity of the association? - Are there statistically significant differences in the behavior of citizenship due to the variable function? - What is the level of citizenship behavior among the members of the active associations in Ain El-Melh Municipality?
Keywords: Society, Assembly activity, Citizenship.